2017
DOI: 10.1111/jch.12950
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of a multi‐community hypertension implementation study: the American Heart Association's Check. Change. Control. program

Abstract: Single-site, intensive, community-based blood pressure (BP) intervention programs have led to BP improvements. The authors examined the American Heart Association's Check. Change. Control. (CCC) program (4069 patients/18 cities) to determine whether BP interventions can effectively be scaled to multiple communities, using a simplified template and local customization. Effectiveness was evaluated at each site via site percent enrollment goals, participant engagement, and BP change from first to last measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Several prior studies have demonstrated that the use of screening, health education and self-monitoring can promote improved hypertension control. [5,[7][8][9][10]14] In 2013, The AHA launched CCC program as an evidencebased hypertension management program that utilizes blood pressure self-monitoring to empower patients/participants to take ownership of their cardiovascular health. The CCC programs depends on volunteer health mentors to carry out the programs and interact with program participants; these volunteer health mentors were from both healthcare and nonhealthcare backgrounds.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several prior studies have demonstrated that the use of screening, health education and self-monitoring can promote improved hypertension control. [5,[7][8][9][10]14] In 2013, The AHA launched CCC program as an evidencebased hypertension management program that utilizes blood pressure self-monitoring to empower patients/participants to take ownership of their cardiovascular health. The CCC programs depends on volunteer health mentors to carry out the programs and interact with program participants; these volunteer health mentors were from both healthcare and nonhealthcare backgrounds.…”
Section: Discussionmentioning
confidence: 99%
“…The positive results of this study support the findings of previous studies that investigated the CCC program. [12,13] The extremely positive effects of this project are an eyeopening on the need of applying the program on a larger scale and invite other nursing programs in the region and US to participate in CCC program. To apply this program on a larger scale, partnerships with community organizations such as community health and wellness centers are needed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations